2014
DOI: 10.1007/s10646-014-1350-3
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of HgCl2 on activities of SOD, AchE and relative expression of SOD, AChE, CYP1A1 of zebrafish

Abstract: In order to explore the impact of mercury on fish, zebrafish were exposed in various levels of HgCl2 and the superoxide dismutase (SOD), acetylcholinesterase (AChE) activities were measured after 1 and 7 days exposure. Muscle RNA was also extracted for semi-quantitative RT-PCR determination of the expression of AChE, CYP1A1, Cu/Zn-SOD. It indicated that 96 h-LC50 of HgCl2 to zebrafish is 244.06 µg L(-1). The AChE activity was decreased on 1st day and 7th day. The SOD activity was almost unchanged on 1st day, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Results of the measurement of SOD and CTL GFP reporters evidenced that there were no significant enzymatic modulation when worms were treated only with the butiá extract, which lead us to believe that the antioxidant effect observed is due to direct interaction between extracts compounds and ROS (Figure ). Also, antioxidant enzymes induction is commonly suggested as a toxicity parameter, since their needing would indicate some sort of intracellular imbalance (Agus, Sumer, & Erkoc, ; Gemelli et al, ; Zhen et al, ). Then, lack of SOD and CTL induction may also be another indicative of butiá's extract low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the measurement of SOD and CTL GFP reporters evidenced that there were no significant enzymatic modulation when worms were treated only with the butiá extract, which lead us to believe that the antioxidant effect observed is due to direct interaction between extracts compounds and ROS (Figure ). Also, antioxidant enzymes induction is commonly suggested as a toxicity parameter, since their needing would indicate some sort of intracellular imbalance (Agus, Sumer, & Erkoc, ; Gemelli et al, ; Zhen et al, ). Then, lack of SOD and CTL induction may also be another indicative of butiá's extract low toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In Zebra sh, low dose (0.1 LC50) of HgCl 2 increased CYP1A1, but at higher doses (0.4 and 0.8 LC50), the expression of CYP1A1 was suppressed [36]. Zuotai at the concentration of 0.2 mg/mL (below LC50) could increase CYP1A1 and CYP1B1 in Zebra sh [36]. In the mouse heart, kidney and lung, HgCl 2 (2.5 mg/kg, ip) increased CYP1A1, along with other CYP450 isoforms [37].…”
Section: Zuotai In Tibetan Medicinesmentioning
confidence: 93%
“…In comparison, the effects of HgCl 2 on CYP1A expression were more dramatic. In Zebra sh, low dose (0.1 LC50) of HgCl 2 increased CYP1A1, but at higher doses (0.4 and 0.8 LC50), the expression of CYP1A1 was suppressed [36]. Zuotai at the concentration of 0.2 mg/mL (below LC50) could increase CYP1A1 and CYP1B1 in Zebra sh [36].…”
Section: Zuotai In Tibetan Medicinesmentioning
confidence: 94%
“…Previous studies also revealed that SOD genes were involved in response to toxic challenge. For instance, in zebrafish, researchers found that low concentrations of toxic HgCl 2 exposure could significantly induce the expression of Cu/Zn-SOD in muscle, with dose-dependent enhancement of SOD activity [15]. In muscle afferent DRG (dorsal root ganglia) neurons of rats, a lower superoxide level owing to the addition of SOD could modulate the current of voltage-gated sodium channels (Na v ), the main target site under tetrodotoxin stress [16].…”
Section: Introductionmentioning
confidence: 99%